Correlation between Microbial Community and Volatile Flavor Substances in Seven Rice-flavored Baijiu Xiaoqu - Hui HOU; Junguang HAO; Umer Javed HAFIZ; Ruijie WAN; Ziru DAI; Long ZHANG; Chunguang ZHANG; Cen QI (Shipin gongye ke-ji)
The relationship between microbes and volatile flavor in various rice-flavored Baijiu Xiaoqu (rfBX) was investigated using high-throughput sequencing technology and headspace solid-phase microextraction-gas chromatography-mass spectrometry (HSPME-GC-MS) to analyze the microbial community structure and composition of volatile organic compounds (VOCs), respectively. In this study, the outcome revealed that seven types of rfBX sourced from Guangxi, China, contained 10 dominant fungus genera, 42 key bacterial genera (where dominant genera were those with a relative abundance greater than 1%), of which Saccharomycopsis and Aspergillus were the main dominant fungal genera. Weissella and Pediococcus were the main bacterial genera. The results of principal component analysis showed that the microbial community composition was most similar in Xiaoqu C and Xiaoqu D. A total of 104 VOCs were detected. Among VOCs, 1-octen-3-ol, linalool, and phenylethanol were detected in all samples of Baijiu Xiaoqu. Furthermore, the correlation analysis indicated that the dominant microbial genera with a significant correlation with VOCs were Trichoderma, Monascus, Candida, Bacillus, Klebsiella, and Pantoea. These results highlighted the substantial impact of dominant microbial genera on the volatile flavor profile of Baijiu Xiaoqu, serving as a valuable reference for optimizing microbial species and enhancing the quality of rfBX in the industry of Guangxi, China.